Applying the difference operators for surfaces approximation with given accuracy in nodes - Shtunder, Oksana; Manzhula, Volodymyr; Kasatkina, Natalya (Видавництво Львівської політехніки, 2012)
A method of surfaces approximation with given accuracy in nodes by difference operator using the methods of interval data analysis described in this paper.
Keywords: interval data analysis; surface approximation; difference operator